Ответ:
Объяснение:
Наконец-то дошел до решения:
слева вынесем sinx, справа -sqrt(3)/2:
sinx(1 -
* cosx) = -
*(1 -
* cosx)
Перенесем все влево: (1 -
* cosx) * (sinx +
) = 0
1) sinx = -![\frac{\sqrt{3} }{2} \frac{\sqrt{3} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B3%7D%20%7D%7B2%7D)
1. x = 4pi/3 + pi*n, n∈Z
2. x= -pi/3 + pi*n, n∈Z
2) cosx = ![\frac{\sqrt{3} }{2} \frac{\sqrt{3} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B3%7D%20%7D%7B2%7D)
1. x= pi/6 + 2pi*n, n∈Z
2. x = -pi/6 + 2pi*n, n∈Z